Cross-cultural adaptation and validation of the "Spinal Cord Injury-Falls Concern Scale" in the Italian population. Issue 7 (July 2018) - Marquez, Maria; Santis, Rita; Ammendola, Viviana; Antonacci, Martina; Santilli, Valter; Berardi, Anna; Valente, Donatella; Galeoto, Giovanni
Abstract Study design Psychometrics study. Objective The objective of this study was to develop an Italian version of the Spinal Cord Injury-Falls Concern Scale (SCI-FCS) and examine its reliability and validity. Setting Multicenter study in spinal units in Northern and Southern Italy. The scale also was administered to non-hospitalized outpatient clinic patients. Methods The original scale was translated from English to Italian using the "Translation and Cultural Adaptation of Patient-Reported Outcomes Measures" guidelines. The reliability and validity of the culturally adapted scale were assessed following the "Consensus-Based Standards for the Selection of Health Status Measurement Instruments" checklist. The SCI-FCS-I internal consistency, inter-rater, and intra-rater reliability were examined using Cronbach's alpha coefficient and the intraclass correlation coefficient, respectively. Concurrent validity was evaluated using Pearson's correlation coefficient with the Italian version of the short form of the Wheelchair Use Confidence Scale for Manual Wheelchair Users (WheelCon-M-I-short form). Results The Italian version of the SCI-FCS-I was administered to 124 participants from 1 June to 30 September 2017. The mean ± SD of the SCI-FCS-I score was 16.73 ± 5.88. All SCI-FCS items were either identical or similar in meaning to the original version's items. Cronbach's α was 0.827 (p  < 0.01), the inter-rater reliability was 0.972 (p  < 0.01), and the intra-rater reliability was 0.973 (p  < 0.01). Pearson's correlation coefficient of the SCI-FCS-I scores with the WheelCon-M-I-short form was 0.56 (p  < 0.01). Conclusions The SCI-FCS-I was found to be reliable and a valid outcome measure for assessing manual wheelchair concerns about falling in the Italian population.